PBG 4. A Promising vegetable Pigeonpea variety released for Ilocos Region (2018)
The National Seed Industry Council (NSIC) released a new variety of pigeonpea or kadios (Cajanus cajan L.), one of the climate resilient crops ideal for the Ilocos Region and have similar performance in other regions of the country. A variety adaptable to year-round production under all soil conditions including marginal areas especially in Regions 1,2, and 3 pigeonpea growing areas. ICP 7035 (MMICRIP WMJ) was derived following selection method from the germplasm collection at ICRISAT, Hyderabad, India. It was introduced in the Philippines with legitimate supporting documents as required in the Materials Transfer Agreement (MTA). The purity was maintained through selections made by researchers at MMSU. Series of trials in accordance with the regulations of the NSIC were done. Yield and yield characteristics are far superior to the local varieties being used by farmers. It has an average seed yield of 1.282-2.0 tons per hectare which is significantly higher than the local check with 0.516 tons per hectare. It has non-determinate growth habit with yellow-red colored flowers. It flowers in 96 days and matures in 142 days while the local check flowers in 130 days and matures in 201 days. The seeds are sweet due to higher sugar content. It can be marketed as immature pods for vegetable purpose. It is found to be resistant to diseases like Sterility mosaic, Cercospora leaf spot, rust and other pests prevalent in legumes.